Takaful: an ideal alternative for women - Abdullah, Nurdianawati Irwani (International Shari'ah Research Academy for Islamic Finance (ISRA), 2012)
This paper is motivated by the present facts, that women play significant and extensive roles that are not confined to their traditional household duties. This is partly due to increasing financial demands as the definition of families’ essential needs has expanded. The rising cost of living has made surviving and building a family on a single income near to impossible. Therefore, women are forced to take on some of the ﬁnancial burdens in the management and maintenance of a household, in addition to their core responsibilities as wives and mothers. To perform these multi-tasking responsibilities, they have to be very wise, energetic and efficient.